2006
DOI: 10.11120/jebe.2006.01020070
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies among Construction Professionals: Cognitive and Behavioural Efforts to Manage Job Stressors

Abstract: Construction professionals are constantly exposed to varying stressors in their working environment and are likely to experience a high level of job burnout. Burnout threatens the mental and physical health of individuals and also decreases levels of job satisfaction and productivity. Research relating to managing job burnout has so far concentrated mainly on identifying job-related factors which are associated with burnout. Coping strategies affect the cognitive and behavioural efforts an individual exerts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Problem-solving behavior deliberates problem-focused efforts to change the situation (Newton and Keenan, 1985;Yip and Rowlinson, 2006). It deals directly with the problem and its effects, as well as caters to time management, management skills and making selfadjustments (Leung et al, 2012).…”
Section: Problem-focused Coping Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…Problem-solving behavior deliberates problem-focused efforts to change the situation (Newton and Keenan, 1985;Yip and Rowlinson, 2006). It deals directly with the problem and its effects, as well as caters to time management, management skills and making selfadjustments (Leung et al, 2012).…”
Section: Problem-focused Coping Behaviormentioning
confidence: 99%
“…It deals directly with the problem and its effects, as well as caters to time management, management skills and making selfadjustments (Leung et al, 2012). Yip and Rowlinson (2006) indicated that planned problemsolving is the most commonly embraced coping method for construction professionals. Positive re-appraisal is a coping strategy that individuals adopt for cognitive adjustments to a situation (Lazarus and Folkman, 1984).…”
Section: Problem-focused Coping Behaviormentioning
confidence: 99%
See 3 more Smart Citations